ER Stress Induced by Artemisinin and Its Derivatives Determines the Susceptibility to Their Synergistic Apoptotic Killing With TRAIL - Snigdha Bhowmick; Yong J. Lee (Cancer Medicine)
ABSTRACT Aim Artemisinins are a class of antimalarial drugs that are lately being researched for their antitumor activity. We previously reported that artesunate, an artemisinin derivative, can induce ferroptosis and enhance TRAIL (Tumor necrosis factor‐Related Apoptosis‐Inducing Ligand)‐induced apoptosis. Here we investigated the role of endoplasmic reticulum (ER) stress induced by artemisinin and its derivatives, especially in the enhancement of TRAIL‐induced apoptosis, which can be exploited for repurposing the use of artemisinins in cancer therapy. Methods We show in this study a comparative profile of the ER stress induced by different derivatives of this drug, namely artemisinin, artesunate, arteether, artemether, and dihydroartemisinin, all of which are available readily and approved for treating human patients. These five derivatives were used to treat human colon carcinoma HCT116 cells and pancreatic adenocarcinoma BxPC3 cells over a range of doses. Results Our data show a highly significant positive correlation between ER stress caused by these drugs and their corresponding apoptotic susceptibilities upon treatment with TRAIL. Conclusion We concluded that dihydroartemisinin is the most effective contender among all the derivatives tested to enhance TRAIL‐induced apoptosis.